PENGARUH SOSIAL MEDIA MARKETING DAN KETERLIBATAN MEREK PELANGGAN YANG EMOSIONAL TERHADAP LOYALITAS MEREK - Salsabila Dwi Putri; Yolanda Masnita (STMIK Widuri Jakarta, 2025)
With the rapid advancement of technology today, business owners, consultants, and marketing managers are increasingly aware of the increasing use of social media. Marketing through social media has different characteristics compared to traditional marketing methods, so it requires special attention and a planned strategy to build brand image and loyalty. This study aims to analyze whether social media marketing and emotional customer brand engagement have an effect on brand loyalty. The researcher used a quantitative research method with a survey technique using a questionnaire as a research data collection technique. There are 25 questionnaire items related to the influence of social media marketing and emotional customer brand engagement on brand loyalty. The research data were analyzed using SPSS (Statistical Product and Service Solutions). The results of the research show that social marketing media and consumers' emotional involvement with brands have a positive effect on brand loyalty.